\(λ\)-\(Δ^m\)-Statistical Convergence on Intuitionistic Fuzzy Normed Spaces - Antal, Reena; Chawla, Meenakshi (Communications in Mathematics and Applications, 2023)
The basic purpose of our work is to define λ-statistical convergence for the generalized difference sequences (i.e. \(λ\)-\(Δ^m\)-statistical convergence) on Intuitionistic Fuzzy Normed space (IFN space). We have proven topological results about this generalized method of sequence convergence. Also, we have given the \(λ\)-\(Δ^m\)-statistical Cauchy sequences along with its Cauchy criteria of convergence on these spaces.